China’s Quest for Legal Modernity - Gellhorn, Walter (Columbia Journal of Asian Law, 1987)
Chinese law today is in a state of amazing efflorescence. Systematization of legal propositions is not, however, a newcomer in China nor is law administration a lately developed concern of an authorita- rian state. On the contrary, awareness of laws and of lawfulness existed long ago. Documents of the later years of the Zhou dynasty (1122-256 B.C.) evince considerable sophistication about legal obligations, and the Emperor in that distant time left little doubt about who was in charge of law administration throughout the imperial realm. Instances of technically advanced lawmaking in Chinese antiquity occasionally strike the eye. Centuries ago, for example, the legal rights and duties of mortgagors and mortgagees had been clearly delineated. In that instance the purpose was not to resolve conflicts between opposing interests, but to assist the imperial tax collector in identifying whom he should pursue. The bulk of ancient law, in fact, seems to have been designed to reinforce the duties owed to one’s elders and betters, and above all to the Emperor; inter-personal relations were largely left to the customary regulations of locality and family – bearing always in mind the generally accepted Confucian proposition that the loftier and older a person became, the greater became the likelihood of his being right. Even under the penal law of the early twentieth century, a father could kill his son without incurring much more than a reproof and a warning, while a son who killed his father, or even his only slightly older brother, faced a very hard time. Only the killing of friend by friend came to court on an even keel, so to speak. Matters of little imperial concern – and those included most of what is nowadays regarded as the Civil as distinct from the Criminal Law – were left to supposedly shared moral values coupled with private lawmaking through the formation of contracts (both commercial and matrimonial). The processes of conciliation, adjustment, and compromise, rather than the rulings of state organs, were relied upon if later disputes were to arise; custom, not law, was the determinant of rights.